Alinhamento temporal de sequências de vídeo adquiridas por câmeras perspectivas e catadióptricas - Geraldo Augusto Massahud Rodrigues dos Santos (2006)
This work adresses the problem of estimating the temporal alignment between 2 unsynchronized video sequences of the same dynamic 3D scene, captured from distinct viewpoints by a perspective camera and a catadioptric camera. We present a method that is an extension of an existing technique for temporal aligning multiple video sequences acquired by perspective cameras. Experimental results with real world sequences show that our method can accurately align the videos even when they have large misalignments. Finally, experimental results with synthetic sequences show how our method behaves in the presence of errors in the system.